Sharing the burden for climate change mitigation in the Canadian federation - Christoph Böhringer; Nicholas Rivers; Thomas F. Rutherford; Randall Wigle (University of Oldenburg, Department of Economics, 2014)
Dividing the burden for greenhouse gas abatement amongst the provinces has proven challenging in Canada, and is a major factor contributing to Canada's poor historic performance on greenhouse gas abatement. As the country aims to achieve substantial cuts to emissions over the next decade and by mid-century, such burden sharing considerations are likely to be elevated in importance. This paper uses a calibrated multi-region multi-sector computable general equilibrium model to compare a number of archetypal rules for sharing the burden of a joint commitment amongst members for the case of greenhouse gas reductions in Canada. Because of the substantial heterogeneity amongst Canadian provinces, these different burden sharing rules imply signifcantly different relative abatement effort amongst provinces, and also signifcantly different welfare implications. When emission permits are allocated on an equal per capita basis, welfare is increased in Ontario, British Columbia, Quebec, and Manitoba, and signifcantly reduced in Alberta and Saskatchewan. In contrast, when emission permits are allocated based on historic emissions, Alberta and Saskatchewan are made better off, and Ontario, British Columbia, Quebec, and Manitoba are made worse off. We compare these archetypal burden sharing rules to existing provincial emission reduction commitments, and find that none of the standard burden sharing rules comes close to existing commitments. We argue that the debate on burden sharing of greenhouse gas abatement in Canada could be objectified if informed by coherent quantitative analysis such as the one presented here.
Keywords: C68; Q50; 330; climate; burden sharing; computable general equilibrium analysis; Klimawandel; Treibhausgas; Klimaschutz; Soziale Kosten; Verteilungswirkung; Allgemeines Gleichgewicht; Mehr-Sektoren-Modell; Kanada